CompTIA Linux+ certification guide : a comprehensive guide to achieving LX0-103 and LX0-104 certifications with mock exams - Inshanally, Philip (Packt Publishing Ltd, 2018)
CompTIA certified professionals have always had the upper hand in the information technology industry. This book will be your ideal guide to passing and achieving the Linux+ certification efficiently. Learn from industry experts and implement their practices to resolve complex IT issues.